Step-by-step explanation:
An exponential function has the form:
y = a · b^x
Are you sure you copied the problem correctly? Perhaps instead of minus, you meant multiplication:
f(x) = 620 · 7.8^x
If so, then a = 620 and b = 7.8.
Answer:
Step-by-step explanation:
60
X must be increased by 6 to get its value to be 0. Then the corresponding change in y will be (-2/3)*6 = -4. That value added to -5 makes it -9.
The y-intercept will be -9.
To solve for f, you need to isolate/get the variable by itself in the equation:
4(0.5f - 0.25) = 6 + f Distribute 4 into (0.5f - 0.25)
(4)0.5f + (4)(-0.25) = 6 + f
2f - 1 = 6 + f Subtract f on both sides to get "f" on one side of the equation
2f - f - 1 = 6 + f - f
f - 1 = 6 Add 1 on both sides to get "f" by itself
f - 1 + 1 = 6 + 1
f = 7
PROOF
4(0.5f - 0.25) = 6 + f Substitute/plug in 7 into "f" since f = 7
4(0.5(7) - 0.25) = 6 + 7
4(3.5 - 0.25) = 13
4(3.25) = 13
13 = 13
Answer:
x + 8
Step-by-step explanation:
x + 5 + 3.
add the numbers
↓
x + 8